'Tis pity she's a whore - Ford, John, 1586-approximately 1640 (Routledge English texts., 1997)
The last decade has seen a revival of interest in John Ford and especially 'Tis Pity She's a Whore, his tragedy of religious scepticism, incestuous love, and revenge. This text in particular has provided a focus for scholarship as well as being the subject of a number of major theatrical productions. Simon Barker guides the reader through the full range of previous interpretations of the play; moving from an overview of traditional readings he goes on to enlarge upon new questions that have arisen as a consequence of critical and cultural theory.